Integrasi Kearifan Lokal Cerita Takyat Joko Tole Dalam Pembelajaran Untuk Menanamkan Nilai Nasionalisme Dan Cinta Tanah Air - Fanny Rahmawan; Muhammad Rafly Eka Prasetya; Ahmad Hasbi Ashidiqi; Agung Setyawan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to analyze the integration of local wisdom from the Joko Tole folklore into learning as an effort to instill the values of nationalism and patriotism among elementary school students. This research employs a qualitative approach with an ethnopedagogical study design. The data sources include the Joko Tole folklore text, scientific literature, and educational policy documents. The instruments used consist of a literature data recording sheet, a content analysis form, and a data classification guide. Data were analyzed through data reduction, classification and categorization, interpretation, and conclusion drawing. The results show that the Joko Tole folklore contains values of courage, loyalty, responsibility, hard work, and devotion to the region, which are relevant for character education in elementary schools. These values can be integrated into various subjects such as Civics, Indonesian Language, Social Studies, Science, and Arts and Culture. This integration not only fosters pride in national culture but also strengthens students’ sense of nationalism and love for the homeland. Therefore, local wisdom–based learning through the Joko Tole story serves as an effective strategy to preserve cultural heritage while cultivating a spirit of patriotism aligned with the Pancasila Student Profile and the goals of national education.